Self-Spreading Biotechnology and International Law Prevention, Responsibility, and Liability in a Transboundary Context - Beck, Felix (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, 2022)
Who is liable if self-spreading biotechnology causes transboundary harm? With engineered gene drives and similar techniques, the genes of wild-living species, pathogens, and crop plants can soon be modified directly in the environment. This might help address pressing public health, environmental, and food security problems. However, these techniques may also spread across national borders. Looking at both states and private actors, this book studies the rules of international law on the prevention of, and liability for, adverse transboundary effects caused by self-spreading biotechnology. Through an in-depth analysis of the relevant treaties and custom, it shows that international law is not yet equipped to cope with the challenges ahead.